Coconut Wood Density Image Processing Techniques Based On Texture Image With Comparison Of Sobel Edge Detection Algorithm And Canny Edge Detection Algorithm - Aulia Annisa Br Bangun; Achmad Fauzi; Husnul Khair (International Journal of Health Engineering and Technology, 2022)
Indonesia is the second largest country that has Cocos nucifera coconut trees, coconut wood has a strength that is not inferior to existing forest wood, other building elements and for mabel and building construction materials. Coconut wood also has unique fibers, so it has a high aesthetic value. The quality of coconut wood, namely strength and durability, is determined by many factors, one of which is the pattern of fiber density in coconut wood. How to find out the density of coconut wood digitally by detecting the outer patch of coconut wood using a computer so that it can make it easier and help determine the image of quality coconut wood. To determine the quality of coconut wood by looking at the fiber density by reducing noise before calculating the edge detection so that more edges are produced. By checking the numbers if the value of the number >= 128 then the binary value given is 1, if the value of the number < 128 then the binary value given is 0, then the binary value given for the numbers 12,12,10 is 0,0,0. And By checking the numbers if the value of the number >= 128 then the binary value given is 1, if the value of the number < 128 then the binary value given is 0, then the binary value given for the numbers 12,29,-28 is ,0,0, 0.